Inflammation in human adipose tissues–Shades of gray, rather than white and brown. (December 2018) - Rakotoarivelo, Volatiana; Variya, Bhavesh; Ilangumaran, Subburaj; Langlois, Marie-France; Ramanathan, Sheela
Highlights: There are no cytokines that are consistently associated with obesity in humans. Unlike in murine models, IL-4 is associated with obesity in humans. Cellular stress caused by excess energy intake can activate signaling pathways that induce inflammation. Inflammation is a consequence rather than primary cause of insulin resistance. Abstract: Chronic inflammation in adipose tissues has been associated with obesity and metabolic syndrome over the years. Various studies using animal models have contributed to our knowledge on the pro- and anti- inflammatory mediators that regulate obesity. Analyses of cytokine profiles in humans have not revealed a clear scenario. Likewise, treatments targeting inflammation to control obesity and insulin resistance has not yielded promising results. In this review we summarize the data available in human obesity and discuss the possible reasons that could explain the difficulties in treating obesity and insulin resistance by targeting pro-inflammatory cytokines.